2014
DOI: 10.1371/journal.pone.0108232
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Receptor Activation Increases HIV Entry into Primary Human Macrophages

Abstract: Macrophages are the primary cell type infected with HIV in the central nervous system, and infection of these cells is a major component in the development of neuropathogenesis and HIV-associated neurocognitive disorders. Within the brains of drug abusers, macrophages are exposed to increased levels of dopamine, a neurotransmitter that mediates the addictive and reinforcing effects of drugs of abuse such as cocaine and methamphetamine. In this study we examined the effects of dopamine on HIV entry into primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
78
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 156 publications
6
78
0
1
Order By: Relevance
“…In contrast to its role in preventing sepsis, macrophage exposure to dopamine may increase susceptibility to HIV [20, 21]. Macrophages are the main cell type in the CNS that are infected with HIV, and recent studies showed that dopamine treatment of human peripheral blood monocyte-derived macrophages led to a two-fold increase in CCR5-mediated HIV entry and increased HIV replication.…”
Section: Catecholaminesmentioning
confidence: 99%
“…In contrast to its role in preventing sepsis, macrophage exposure to dopamine may increase susceptibility to HIV [20, 21]. Macrophages are the main cell type in the CNS that are infected with HIV, and recent studies showed that dopamine treatment of human peripheral blood monocyte-derived macrophages led to a two-fold increase in CCR5-mediated HIV entry and increased HIV replication.…”
Section: Catecholaminesmentioning
confidence: 99%
“…Compared with non-users, HIV patients who are drug users exhibit increased frequency of HIV-encephalitis [135]. Some of the drugs, such as cocaine and methamphetamine, exert addictive and reinforcing effects via increased extracellular dopamine level in the brain, while altered activity of dopamine and dopamine receptors has been implicated in the pathogenesis of HIV-1 in terms of viral entry and replication [112,136]. Other factors that facilitate HIV viral entry includes disruption in the integrity of blood-brain barrier (BBB).…”
Section: Autophagy In Hiv-1 With Co-exposure Of Doamentioning
confidence: 99%
“…In the early stage of HIV infection, increased levels of DA and decreased DA turnover are found in the cerebrospinal fluid of therapy-naĆÆve HIV patients with asymptomatic infection12, which may contribute to decreased levels of DA in DA-rich brain regions81314 in the advanced stages of HIV infection. Importantly, HIV-induced elevated levels of extracellular DA in the CNS can stimulate viral replication in human macrophages within DA-rich brain regions151617, resulting in viral protein release. It is commonly accepted that viral replication and proteins within the CNS are correlated with the persistence of HIV-related neuropathology and subsequent neurocognitive deficits18192021.…”
mentioning
confidence: 99%